Implementation Of The A* (A-Star) Algorithm For Website-Based Search Of Tourism Sites In The City Of Bengkulu - Ahmad Abdul Maliq; Yulia Darmi; Dwita Deslianti; AR. Walad Mahfuzi (Jurnal Komputer, Informasi dan Teknologi, 2023)
This study is entitled the implementation of the a* (a-star) algorithm for website-based search of tourism sites in the city of Bengkulu. The main problem ishow to build an information system search for the nearest tourism location in the city of Bengkulu. Information Systems search for this tourism locationusing the a* (a-star) algorithm method and this information system also displays information about existing tours. The a* (a-star) algorithm method was chosen because this method determines the shortest path between the starting and ending points of an existing tour. Based on the results of the discussionThe A-star algorithm is considered more effective in finding the shortest route. This is proven by testing the shortest route randomly and thoroughly 15 times for all tourist destinations. The results show that the routes generated on average are more effective and shorter than the routes generated on Google Maps.